The Mutational Landscape of Early-Onset Breast Cancer: A Next-Generation Sequencing Analysis - Andrikopoulou, Angeliki; Chatzinikolaou, Spyridoula; Kyriopoulos, Ilias; Bletsa, Garyfalia; Kaparelou, Maria; Liontos, Michalis; Dimopoulos, Meletios-Athanasios; Zagouri, Flora (Frontiers in Oncology, 2022)
Around 5%–7% of breast cancer cases are diagnosed in women younger than 40, making it the leading cause of female cancer in the 25- to 39-year-old age group. Unfortunately, young age at diagnosis is linked to a more aggressive tumor biology and a worse clinical outcome. The identification of the mutational landscape of breast cancer in this age group could optimize the management. Recently, next generation sequencing (NGS) has enabled the detection of a broad spectrum of mutations and the molecular characterization of early-onset breast cancer. We performed NGS analysis in paraffin blocks and blood samples of 32 young patients with breast cancer [<40 years] and 90 older patients during the period 2019 through 2021. All patients were treated in a single institution at the Oncology Department of “Alexandra” Hospital, Medical School, University of Athens, Greece. Breast tumors were characterized more frequently by HER2 overexpression [25% vs 18.9%], higher ki67 levels [75% vs 61%] and lower differentiation [71.9% vs 60%] in the younger group. PIK3CA [6/20; 30%] and TP53 [6/20; 30%] were the most frequent pathogenic somatic mutations identified in young patients, while one case of BRCA2 somatic mutation [1/20; 5%] and one case of PTEN somatic mutation [1/20; 5%] were also identified. PIK3CA mutations [16/50; 32%] and TP53 mutations [20/50; 40%] were the most common somatic mutations identified in older patients, however other somatic mutations were also reported (ATM, AKT, CHEK2, NRAS, CDKN2A, PTEN, NF1, RB1, FGFR1, ERBB2). As for germline mutations, CHEK2 [3/25; 12%] was the most common pathogenic germline mutation in younger patients followed by BRCA1 [2/25; 8%]. Of note, CHEK2 germline mutations were identified less frequently in older patients [2/61; 3%] among others (BRCA1 [2/61; 3%], ATM [2/61; 3%], APC [1/61; 1,6%] and BRCA2 [1/61; 1,6%]). Young patients with breast cancer harbor a distinct mutational profile than their older counterparts. We here report the mutational profile identified via NGS in patients with early-onset breast cancer compared to their older counterparts. Although the sample size is small and no statistically significant differences were detected, we highlight the need of genetic testing to most patients in this subgroup.